2016
DOI: 10.1007/s10620-016-4356-2
|View full text |Cite|
|
Sign up to set email alerts
|

Vedolizumab Therapy Is Associated with an Improvement in Sleep Quality and Mood in Inflammatory Bowel Diseases

Abstract: Introduction Poor sleep, depression, and anxiety are common in patients with inflammatory bowel diseases (IBD) and associated with increased risk of relapse and poor outcomes. The effectiveness of therapies in improving such psychosocial outcomes is unclear but is an important question to examine with increasing selectivity of therapeutic agents. Methods This prospective cohort enrolled patients with moderate-to-severe CD or UC starting biologic therapy with vedolizumab or anti-tumor necrosis factor α agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 59 publications
(59 reference statements)
1
31
0
1
Order By: Relevance
“…The link between corticosteroid use and poor sleep might represent one argument for opting for corticosteroid-sparing agents in targeting the control of IBD activity. Moreover, a prospective study conducted by Stevens and collaborators demonstrated that the use of anti-TNF therapy and vedolizumab might even lead to an improvement in sleep, depression, and anxiety in patients with moderate to severe IBD, highlighting this aspect within 6 weeks of therapy, which was maintained up to 1 year [19]. Among the other types of medication in our IBD patient group, there was no statistically significant difference in PSQI scores, which might suggest that this type of medication is either associated with a less severe disease phenotype (aminosalicylates) or with a better control of disease activity and less psychological distress (biological therapy and azathioprine).…”
Section: Discussionmentioning
confidence: 99%
“…The link between corticosteroid use and poor sleep might represent one argument for opting for corticosteroid-sparing agents in targeting the control of IBD activity. Moreover, a prospective study conducted by Stevens and collaborators demonstrated that the use of anti-TNF therapy and vedolizumab might even lead to an improvement in sleep, depression, and anxiety in patients with moderate to severe IBD, highlighting this aspect within 6 weeks of therapy, which was maintained up to 1 year [19]. Among the other types of medication in our IBD patient group, there was no statistically significant difference in PSQI scores, which might suggest that this type of medication is either associated with a less severe disease phenotype (aminosalicylates) or with a better control of disease activity and less psychological distress (biological therapy and azathioprine).…”
Section: Discussionmentioning
confidence: 99%
“…In IBD, observational studies of patients with CD and UC newly-commenced on either anti-TNF therapy or vedolizumab have demonstrated improved depression scores following treatment. 71,76 However, neither of these studies accounted for the potential confounding effect of glucocorticosteroid tapering on psychological wellbeing in their analyses.…”
Section: Conventional Pharmacological Therapiesmentioning
confidence: 99%
“…Considering the effect of inflammation on sleep, it is intuitive that by decreasing disease activity, significant improvement in sleep can be achieved. Patients treated with vedolizumab and anti-TNF medications showed significant improvement in sleep survey scores with reduced nocturnal diarrhea and less abdominal pain [121]. It is also important for clinicians to identify iatrogenic risk factors for sleep impairment and modify treatment regimens.…”
Section: Treatment Of Sleep Disturbancesmentioning
confidence: 99%